Revision of the Metallactus generosus species-group with a preliminary evaluation of the effectiveness of the endophallus morphology in distinguishing critical sibling species (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2020)
A taxonomic revision of the Metallactus generosus species-group is given in the present study. The complex is made up of three Neotropical species, two redescribed here and one new: Metallactus generosus Suffrian, 1866, M. argentinensis Jacoby, 1907 and M. nigroplagiatus new species. Lectotypes are designated for M. generosus and M. argentinensis. An identification key for the species group is provided. The usefulness of endophallic sclerite morphology for taxonomic and diagnostic purposes within the genus Metallactus is briefly discussed. A lapsus calami is corrected, M. chamorroi Sassi, 2019 to M. chamorroae Sassi, 2019,